Odpowiedzi

2010-04-06T21:23:44+02:00
A) 4(3x + 2) + 5 ( 2x + 3 ) = - ( 2x + 13)
12x+8+10x+15=-2x-13
22x+2x=-13-8-15
24x=-36 / :24
x=- 1 i 1/2

b) 4 ( x - 2 ) - 2 ( x - 4 ) = 5 ( x + 1 ) - 3x
4x-8-2x+8=5x+5-3x
2x-5x+3x=5
0x=5 sprzeczne

c) 2 ( x - 4 ) = 2 ( 2x - 1 ) + 6 ( x + 1 )
2x-8=4x-2+6x+6
2x-10x=4+8
-8x=12/*-1
8x=-12 / :8
x=-1 i 1/2

d) 0,2x + 0,3 = 1,3
0,2x=1,3-0,3
0,2x=1 / * 5
x=5

b) 5x - o,8 = 0,1 + 2x
5x-2x=0,1+0,8
3x=0,9 / :2
x=0,3
Najlepsza Odpowiedź!
2010-04-06T21:26:21+02:00
A) 4(3x + 2) + 5 ( 2x + 3 ) = - ( 2x + 13)
12x+8+10x+15=-2x-13
22x+2x=-13-23
24x=-36 /:24
x=-1 1/2

b) 4 ( x - 2 ) - 2 ( x - 4 ) = 5 ( x + 1 ) - 3x
4x-8-2x+8=5x+5-3x
2x-2x=5
0=5
równanie sprzeczne

c) 2 ( x - 4 ) = 2 ( 2x - 1 ) + 6 ( x + 1 )
2x-8=4x-2+6x+6
2x-10x=4+8
-8x=12 /:(-8)
x=-1 1/2

d) 0,2x + 0,3 = 1,3 /*10
2x+3=13
2x=13-3
2x=10 /:2
x=5

b) 5x - o,8 = 0,1 + 2x
5x-2x=0,1+0,8
3x=0,9 /:3
x=0,3